A method for synthesizing electrochemically active oxazine carbon material

The preparation of oxalyne carbon materials through ball milling and mechanochemical reactions solves the problems of complex operation and uncontrollable morphology of existing methods, realizes the synthesis and application of oxalyne carbon materials with controllable structures, and improves the electrochemical performance of lithium-ion batteries.

CN117023561BActive Publication Date: 2025-08-29HENAN AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311159572.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-08-29
Estimated Expiration
2043-09-07

AI Technical Summary

Technical Problem

The existing methods for synthesizing zine-alkyne carbon materials are complex in operation, harsh conditions, uncontrollable in morphology and structure, and difficult to prepare on a large scale.

Method used

The ball milling method is combined with mechanochemical reaction, and calcium carbide and cyanochloride are used as raw materials. By controlling the molar ratio, ball milling time and frequency, azine-alkyne carbon material is prepared, and impurities are removed by washing diluted nitric acid and acetone, and pure azine-alkyne carbon material is finally obtained under freeze-drying.

Benefits of technology

The structure controllable synthesis of oxane carbon materials is achieved, suitable for industrial production, the material has stable C-N heterocycle and high conductivity, and is suitable for electrocatalytic reduction of CO2 and O2 catalysts or catalytic support, improving the electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117023561B_ABST
    Figure CN117023561B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of nano-carbon materials, and in particular to a kind of synthetic method of electrochemically active azine alkyne carbon material. Calcium carbide (CaC2) and cyanuric chloride (C3Cl3N3) are uniformly mixed by synthetic method of the present invention, then added into a ball mill and carried out mechanochemical reaction, and the product obtained is washed with 0.1mol / L dilute nitric acid, acetone and deionized water, and then the washed product is freeze-dried to obtain azine alkyne carbon material. The present invention utilizes cyanuric chloride monomer and calcium carbide to synthesize C N heterocyclic azine alkyne carbon material in a controllable structure for the first time through the method for mechanochemical action, while realizing its morphology and structure controllable preparation; During the process, no solvent is needed, operating conditions are mild, chemical effect is remarkable, principle is simple, raw material cost is low and easy to industrial production, the azine alkyne carbon material obtained is made as lithium ion battery negative electrode material, the performances such as charge and discharge capacity, cycle life of composite material can be improved, and it is of great significance for the development of new energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano-carbon materials, and in particular to a method for synthesizing an electrochemically active azine-alkyne carbon material. Background Art

[0002] With the continuous advancement of modern technology, the global demand for fossil energy is increasing, which not only causes environmental pollution but also has negative impacts on the global climate and human health. Due to the shortage of fossil energy and environmental degradation, it is necessary to develop environmentally friendly and sustainable energy sources (such as wind, solar, tidal, and geothermal energy). However, most of these energy sources are intermittent, necessitating the use of stable and efficient energy storage technologies. Among various energy storage technologies, rechargeable batteries store electrical energy in the form of chemical energy, providing a highly efficient energy management method. Lithium-ion batteries are the most widely researched and applied rechargeable batteries. They use lithium ions as a carrier to store charge and offer advantages such as high energy density, long cycle life, and high operating voltage. However, their low specific energy still cannot meet the development needs of power batteries. It is well known that the performance of energy storage devices depends primarily on the properties of the electrode materials. This has prompted scientists and researchers to explore new anode materials with better lithium ion storage, diffusion, and transport properties.

[0003] Carbon materials are the most widely studied anode materials for lithium-ion batteries, offering advantages such as abundant reserves, low cost, large specific surface area, high conductivity, high charge-discharge capacity, and excellent rate performance. Among them, graphyne, a novel carbon material, has garnered extensive attention and research in recent years. Composed primarily of sp and sp2 hybridized carbon atoms, graphyne exhibits a highly conjugated planar structure, a porous structure, excellent conductivity, and chemical stability. Furthermore, its unique sp hybridization exhibits distinct advantages in lithium storage, such as providing more lithium storage sites, larger nanopores, high ion mobility, and a suitable energy band gap. Similar to graphene, graphyne can also be further modified by heteroatom doping. Among them, nitrogen-rich azinyne, with its regular CN heterocyclic rings, abundant active sites, and enhanced conductivity, is considered a promising new anode material for lithium-ion batteries.

[0004] Currently, methods for synthesizing ordered azine-based carbon materials include interfacial synthesis (liquid-liquid and liquid-gas interfaces), cross-coupling reactions on copper foil, laser coupling reactions, vapor deposition, and solid-phase reactions in air at 120°C. However, these synthetic methods are complex, require harsh conditions, lack controllable morphology and structure, and are difficult to prepare on a large scale. Therefore, developing a structurally controllable CN heterocyclic polyazine-based carbon material and a method for synthesizing such a polyazine-based carbon material with controllable morphology and structure are currently unresolved challenges. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for synthesizing electrochemically active oxazine carbon materials to solve the problems of existing synthesis methods such as complex operation, harsh conditions, uncontrollable morphology and structure, and difficulty in large-scale preparation.

[0006] To achieve the above object, the present invention adopts the following technical solution: a method for synthesizing an electrochemically active oxazine carbon material, comprising the following steps:

[0007] S1. Accurately weigh a certain amount of calcium carbide and cyanuric chloride and mix them evenly;

[0008] S2, transfer the uniformly mixed materials in S1 to a ball mill for mechanochemical reaction;

[0009] S3, washing the product obtained in S2;

[0010] S4. The product after washing in S3 is freeze-dried to obtain the azine carbon material.

[0011] Furthermore, in the S1, the molar ratio of calcium carbide to cyanuric chloride is 1 to 3:1.

[0012] Furthermore, in the S2, the time of the mechanochemical reaction is 2 to 4 hours.

[0013] Furthermore, in the S2, the rotation speed of the ball mill in the ball mill jar is 500-550 rpm, and the operation is alternately performed with a 40-minute run and a 15-minute rest.

[0014] Furthermore, in S2, the ball mill is made of agate.

[0015] Furthermore, in the S3, the product obtained in S2 is washed with 0.1 mol / L dilute nitric acid, acetone and deionized water in sequence, and the washing operation time is controlled to be 3 to 10 minutes.

[0016] Furthermore, in the above-mentioned S4, the freeze-drying temperature is -60 to -50°C, and the freeze-drying time is 24 hours.

[0017] A method for preparing a oxazine / SP composite material comprises the following steps:

[0018] S1, mixing the azine carbon material, conductive carbon black and polyvinylidene fluoride in an N-methylpyrrolidone binder to form a slurry;

[0019] S2, evenly coating the slurry in S1 on the copper foil;

[0020] S3. The copper foil covered with the slurry in S2 is vacuum dried and then sliced ​​to obtain the azine / SP composite material.

[0021] Furthermore, in the S1, the mass ratio of the azine carbon material, the conductive carbon black and the polyvinylidene fluoride is 8:1:1.

[0022] Furthermore, in the above-mentioned S3, the vacuum drying temperature is 60° C. and the drying time is 12 h.

[0023] Beneficial effects of the present invention:

[0024] 1. The reaction process of the present invention does not rely on solvents, has mild operating conditions, significant chemical effects, and requires no additional operation, only ball milling and washing;

[0025] 2. The invention has simple principle, convenient operation, abundant raw materials, low price, economic and environmental protection, and is suitable for industrial production;

[0026] 3. The present invention uses CaC2 as the alkynyl source and cyanuric chloride as the nitrogen-containing precursor to prepare the azine-alkyne carbon material by ball milling. During the preparation process, the material morphology and structure are controlled by regulating the molar ratio of the raw materials, the reaction time, and the ball milling frequency.

[0027] 4. The azine-alkyne carbon material of the present invention has a stable CN heterocycle and pyridine N atom, which can provide active sites for electrocatalytic reduction reactions and improve the conductivity of azine-alkyne carbon. This azine-alkyne carbon material can be potentially used in the fields of catalysts or catalytic supports for the electrocatalytic reduction of CO2 and O2, photocatalytic co-catalysts, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is an X-ray diffraction pattern of the azine-alkyne carbon material prepared in Example 1 of the present invention;

[0029] Figure 2 is a scanning electron microscope image of the azine-yne ​​carbon material prepared in Example 1 of the present invention;

[0030] Figure 3 is a scanning electron microscope image of the azine-yne ​​carbon material prepared in Example 2 of the present invention;

[0031] Figure 4 is a scanning electron microscope image of the azine-yne ​​carbon material prepared in Example 3 of the present invention;

[0032] Figure 5 This is an X-ray photoelectron spectroscopy analysis diagram of the azine-alkyne carbon material prepared in Example 4 of the present invention;

[0033] Figure 6 This is a graph showing the cycle performance of a lithium-ion battery assembled using the azine / SP composite material prepared in Example 5 of the present invention as the negative electrode. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the present invention.

[0035] The principle of the present invention is:

[0036] The azine-acetylene carbon material is prepared by ball milling using CaC2 as the alkynyl source and cyanuric chloride as the carbon-nitrogen heterocyclic precursor. During the preparation process, CaC2 is ground into fine powder and passed through a 200-300 mesh sieve to ensure that it can be fully mixed and contacted with cyanuric chloride, which is conducive to the full progress of subsequent mechanical reactions.

[0037] CaC2 powder and cyanuric chloride undergo a mechanochemical reaction in a ball mill. In order to ensure the purity of the obtained azine-alkyne carbon material, certain requirements are placed on the material of the ball mill. In the actual preparation process, the azine-alkyne carbon material obtained by using a ball mill made of pure agate is superior in purity to the ball mill made of stainless steel. The process effectively eliminates the generation of magnetic impurities (stainless steel tank, steel ball wear), which plays an important role in improving the purity of the azine-alkyne carbon material.

[0038] During the ball milling mechanical reaction process, a large amount of heat will inevitably be generated. In order to ensure safety, the speed of the ball mill in the ball mill jar is 500~550rpm, and it is operated alternately for 40 minutes and 15 minutes intermittently to avoid excessive temperature. The mechanical reaction time is preferably 2~4 hours to obtain the crude product of azine carbon.

[0039] In order to avoid hygroscopic hydrolysis of CaC2, the obtained azine carbon crude product needs to be quickly washed. During the process, 0.1 mol / L dilute nitric acid, acetone and deionized water are used to remove excess impurities such as calcium carbide, calcium salts and cyanuric chloride. The washing should be completed within 3 to 10 minutes. The obtained azine carbon material is then freeze-dried at a temperature of -60 to -50°C for 24 hours to obtain pure azine carbon material.

[0040] Example 1

[0041] A method for synthesizing an electrochemically active oxazine-alkyne carbon material comprises the following steps:

[0042] S1. Accurately weigh 3.21 g (0.05 mol) of finely ground calcium carbide and 3.69 g (0.02 mol) of cyanuric chloride, and mix them evenly.

[0043] S2, then transfer all of it to a dry and clean stainless steel ball mill for mechanochemical reaction for 2 hours;

[0044] S3. After the mechanochemical reaction is completed, the gray product is washed with 0.1 mol / L dilute nitric acid, acetone, and deionized water in sequence to remove excess calcium carbide, cyanuric chloride, and calcium salts;

[0045] S4. The washed gray-black product is placed in a freeze dryer and dried for 24 hours to obtain the azine carbon material.

[0046] Figure 1 The X-ray diffraction pattern of the azine carbon material obtained in Example 1 is shown in FIG. Figure 1 It can be seen that the prepared material is azine carbon, but at the same time, there are impurity peaks at 2Theta=36° and 44°. This is because the chemically pure calcium carbide contained silicon carbide as the raw material. Figure 2 It can be seen that the prepared azine carbon material is in the shape of cubic columns with obvious gaps between the columns.

[0047] Example 2

[0048] A method for synthesizing an electrochemically active oxazine-alkyne carbon material comprises the following steps:

[0049] S1. Accurately weigh 3.21 g (0.05 mol) of finely ground calcium carbide and 3.69 g (0.02 mol) of cyanuric chloride. Use a weighing spoon to briefly mix the two until they have a uniform color.

[0050] S2, then transfer all of it to a dry and clean agate ball mill for mechanochemical reaction for 4 hours;

[0051] S3. After the mechanochemical reaction is completed, the product is washed with 0.1 mol / L dilute nitric acid, acetone, and deionized water in sequence to remove excess calcium carbide, calcium salt, and cyanuric chloride;

[0052] S4. Place the washed product in a freeze dryer and dry for 24 hours.

[0053] According to scanning electron microscopy Figure 3 It can be seen that the prepared azine-alkyne carbon material is in a lamellar shape, and the layers are separated from each other.

[0054] Example 3

[0055] A method for synthesizing an electrochemically active oxazine-alkyne carbon material comprises the following steps:

[0056] S1. Accurately weigh 1.60 g (0.025 mol) of finely ground calcium carbide and 4.62 g (0.025 mol) of cyanuric chloride. Use a weighing spoon to briefly mix the two until they have a uniform color.

[0057] S2, then transfer all of it to a dry and clean agate ball mill for mechanochemical reaction for 4 hours;

[0058] S3. After the mechanochemical reaction is completed, the product is washed with 0.1 mol / L dilute nitric acid, acetone, and deionized water in sequence to remove excess calcium carbide, calcium salt, and cyanuric chloride;

[0059] S4. Place the washed product in a freeze dryer and dry for 24 hours.

[0060] According to scanning electron microscopy Figure 4 It can be seen that the obtained azine-alkyne carbon material is hollow columnar, which is completely different from the morphology of the material obtained in Example 2.

[0061] Example 4

[0062] A method for synthesizing an electrochemically active oxazine-alkyne carbon material comprises the following steps:

[0063] S1. Accurately weigh 3.21 g (0.05 mol) of finely ground calcium carbide and 3.69 g (0.02 mol) of cyanuric chloride. Use a weighing spoon to briefly mix the two until they have a uniform color.

[0064] S2, then transfer all of them to a dry and clean agate ball mill for mechanochemical reaction for 2 hours;

[0065] S3. After the mechanochemical reaction is completed, the product is washed with 0.1 mol / L dilute nitric acid, acetone, and deionized water in sequence to remove excess calcium carbide, calcium salt, and cyanuric chloride;

[0066] S4. Place the washed product in a freeze dryer and dry for 24 hours.

[0067] Figure 5 This is the X-ray photoelectron spectrum analysis diagram of the azin-yne carbon material prepared in Example 4. As can be seen from the figure, the azin-yne carbon material has C at 284.5eV and 285.8eV. C(sp) and C=N(sp2) bonds. At the same time, there is a C=O bond at 289.0 eV, which may be due to the adsorption of H2O and O2 in the air by the azinylated carbon material.

[0068] Example 5

[0069] The electrochemical performance of the azine carbon material synthesized in Example 2 was assembled and tested.

[0070] Azine-based carbon material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) (mass ratio 8:1:1) were mixed in an N-methylpyrrolidone (NMP) binder. The slurry was then evenly coated on copper foil, dried in a vacuum oven at 60°C for 12 hours, and then cut into 12 mm discs. CR (2032) coin cells were prepared in an Ar-filled glove box using a 14 mm lithium sheet as the anode, the azine-based / SP composite as the cathode, a ceramic-modified PP membrane as the separator, and a lithium-ion secondary electrolyte solution of 1 M LiPF6 in DMC:EC:EMC (1:1:1 vol%) as the electrolyte.

[0071] According to the scanning electron microscope image, the azine carbon material prepared in Example 2 is in the form of a sheet and there are also tubes on the sheet ( Figure 3 ).Depend on Figure 6 It can be seen that the lithium-ion battery assembled with the oxazine / SP composite material has a high thermal conductivity at 0.2A g -1 The charge and discharge capacity at the current density of 120 mAhg -1 It gradually increases (the capacity is about 150 mAh g after 80 cycles) -1 ), indicating that the electrochemically active azine-yne ​​carbon materials are suitable as high-performance lithium-ion battery anode materials.

[0072] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, any technical solution that is the same or similar to that of the present application falls within the scope of protection of the present invention.

Claims

1. A method for synthesizing an electrochemically active oxazine-based carbon material, characterized in that: The following steps are involved: S1. Accurately weigh a certain amount of calcium carbide and cyanuric chloride and mix them evenly; The molar ratio of calcium carbide to cyanuric chloride is 1 to 3:1; S2, transfer the uniformly mixed materials in S1 to a ball mill for mechanochemical reaction; The mechanochemical reaction time is 2 to 4 hours; The ball mill in the ball milling jar rotates at a speed of 500-550 rpm, with an alternating operation of 40 min and a rest of 15 min; S3, washing the product obtained in S2; The product obtained from S2 was washed with 0.1 mol / L dilute nitric acid, acetone, and deionized water in sequence, and the washing time was controlled to be 3-10 min; S4. The product after washing in S3 is freeze-dried at -60 to -50°C to obtain the azine carbon material.

2. The method for synthesizing an electrochemically active oxazine-based carbon material according to claim 1, wherein: In the above-mentioned S2, the ball mill is made of agate.

3. The method for synthesizing an electrochemically active oxazine-based carbon material according to claim 1, wherein: In the S4, the freeze-drying time is 24 hours.

Citation Information

Patent Citations

  • Preparation method of graphdiyne carbon material

    CN108083272A